215k views
0 votes
Find the roots of the equation below.

x2 - 6x + 9 = 0

-3
3
±3
±3i

User Aniks
by
6.4k points

2 Answers

3 votes
The answer is just 3 only because if you plug in 3 to subsitute
User PoVa
by
6.1k points
4 votes

Answer:

Roots of the equation x² - 6x + 9 = 0 are 3,3 .

Explanation:

As given the expression in the question be as follow.

x² - 6x + 9 = 0

Simplify the above equation

x² - 3x - 3x + 9 = 0

x (x - 3) - 3 (x -3) = 0

(x - 3)( x - 3) = 0

x = 3, 3

Therefore the roots of the equation x² - 6x + 9 = 0 are 3,3 .

User CLo
by
5.9k points